Research on content distribution mechanism of MP2P networks - Guo-yin ZHANG; Lu LI; Jian-guo SUN; Xiang-hui WANG (Tongxin xuebao)
In consideration of the current MP2P network disturbance from frequent location changes of the mobile nodes,the limited computing power and storage capacity,a flexible strategy of partition management by assigning different functions to nodes according to some standards,regarding a subnet as a unit and using super-nodes to manage subnets were proposed.In order to speed up the data transmission and replacement efficiency,data was processed with partial network coding technology.Additionally,a trans-subnet query algorithm was proposed to link subnets,conduct informa-tion exchange between subnets and resource location.Results of the experiment manifested that this strategy can effi-ciently increase the resource download success rate and hit rate,reduce the average delay,improve the content distribu-tion efficiency of MP2P networks,and simultaneously enhance system robustness.